2018
DOI: 10.11604/pamj.2018.29.60.11931
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of bacterial and fungal pathogen in patients with high risk for invasive fungal disease in an indonesian tertiary care hospital: an observational study

Abstract: IntroductionIn critically ill patients, there is a defect in host defense mechanism resulting in increased susceptibility to bacterial and fungal infection. The pattern of organisms causing infections varies between different countries and hospitals; therefore it is important that every hospital generates antibiograms to guide healthcare professionals during treatment with optimal choice of antibiotics. Our study aimed to described the pattern of fungal and bacterial pathogen in patients with high risk for inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Considering the great importance of studying biofilms under conditions reproducing as much as possible those founded in the environment of different kind of devices used in the medical field, bacterial and yeast attachment and polymicrobial biofilms formed by K. pneumoniae and C. albicans, on the outer surface of those materials were compared [21,22,25].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the great importance of studying biofilms under conditions reproducing as much as possible those founded in the environment of different kind of devices used in the medical field, bacterial and yeast attachment and polymicrobial biofilms formed by K. pneumoniae and C. albicans, on the outer surface of those materials were compared [21,22,25].…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial bloodstream infections are defined as the presence of viable bacteria in the bloodstream that can elicit an immune response [ 9 ]. Bacteria may enter the bloodstream invasion, normally sterile parts of the body, in different ways.…”
Section: Introductionmentioning
confidence: 99%
“…Radji et al found resistance to cephalosporins and quinolones, with retained sensitivity to beta-lactams (meropenem and imipenem) and fosfomycin among Klebsiella pneumoniae and Pseudomonas aeruginosa [35]. A study on antibiotic resistance in Southeast Asia also found high resistance to cephalosporins such as ceftriaxone (88%), ceftazidime (80%), cefepime (72%), and fluoroquinolones namely ciprofloxacin (77%), and levofloxacin (72%) [36]. Due to possible pathogen variation depending on a local institution or region, a comprehensive study about proper empiric antibiotic therapy by analyzing local antibiogram is suggested to optimize the therapeutic effect of antibiotic usage and hence achieve better promotion for antibiotic stewardship programs [6].…”
Section: Discussionmentioning
confidence: 99%